Factors in Immigrant Children's Use of Physician and Dentist Visits, Hospital Care, and Prescribed Medication in the United States - Tyrone C. Cheng; Celia C. Lo (MDPI AG, 2023)
Applying the behavioral model of health services utilization to data from the United States, this study examined immigrant children's use of physician and dentist visits, hospital care, and prescribed medication. We employed data describing 9759 immigrant parents and children who participated in 2021's National Survey of Children's Health. Logistic regression results negatively linked physician visits to child health, child age, Asian children, fathers, lower parent education, lower family income, uninsured children, and parent's U.S. residence under 5 years. Dentist visits were positively associated with child age, girls, Hispanic children, parent education, family income, public/private health insurance coverage, and U.S.-born children, but such use was associated negatively with Asian children. Hospital use was positively associated with poor child health, Black children, children of "other" race/ethnicity, younger parent age, enrolled in health insurance, and parent's U.S. residence under 5 years. The use of prescribed medication was negatively associated with Asian children, younger child age, lower parent education, uninsured child, and lack of English proficiency. The paper's conclusion suggests policymakers expand Medicaid and CHIP eligibility among immigrant children and suggests community education to foster awareness of children's physical and oral health needs and of Medicaid, CHIP, and prescription assistance programs. The conclusion calls for healthcare providers and social workers to accommodate and respect immigrants' traditional health-related beliefs, showing cultural competence.